INOVASI APLIKASI PELAYANAN PELANGGAN (SI AGAN) DI PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA MOEDAL KOTA SEMARANG - Primanto, Aji; Puspitasari, Linda (Berajah Journal, 2025)
The aspect of public service in government bureaucracy and Regional Owned Enterprises is one of the benchmarks of performance. Therefore, it must be able to meet customer expectations and be able to adapt to the demands of the times. This study aims to analyze and describe the Customer Service Application Innovation (SI AGAN) at the Regional Public Water Company Tirta Moedal, Semarang City. The results of the study indicate that the implementation of the customer service application innovation (Si Agan) at Perumda Air Minum Tirta Moedal, Semarang City has been running well. There is relative adventage or relative advantage for both the service provider and the service recipient. In the Si Agan Application, there is compatibility or suitability between the old procedure and the procedures in the application. In addition, the Si Agan application is also in accordance with customer needs. For the complexity or complexity of the Si Agan application, there is no complexity in running the application. All the features in Si Agan are very easy to use. The Si Agan application also meets the element of triability or the possibility of being tested on customers. This application has been tested on several customers in order to find out the shortcomings and fix all these shortcomings. The last factor that is the benchmark for the implementation of innovation is observability or ease of observation. The Si Agan application is an application that is easy to observe and download on the Google Play Store download application.